One or two nation projects? Discourse on inequalities and equality-related policies in South Africa and Brazil - Leubolt, Bernhard (Revista de Sociologia e Política, 2015)
This contribution focuses on the social production and reproduction of social inequalities in Brazil and South Africa. It aims at interlinking different theoretical perspectives and applying them to a comparative analysis of inequality-related policies. Resorting to strategic- relational institutionalism, the historical heritage of discourse formation and the institutionalization of inequality regimes in the two countries to inform the analysis of the more recent conjuncture will be analysed. While South Africa is an example of formal racist discrimination, the Brazilian inequality regime worked on more informal patterns. The different historical heritage influences current foci of equality-related policies, which tend to be dominantly anti-racist in South Africa, while focusing on poverty reduction in Brazil during the recent years. The latter experience tended more towards a discourse of a ‘common interest’ and was better able to institutionalize policies to reduce income inequalities. South Africa is still discursively divided into ‘two nations’. Social uplifting for Africans linked to the governing parties was only partially accompanied by improved living conditions for the poor majority of Africans. Both countries are significantly structured by the respective historical heritage concerning both the creation and the reduction of inequalities. The Brazilian ‘one nation’ discourse was more successful in promoting equality-related policies than its ‘two nations’ counterpart in South Africa. Despite important improvements, both countries are now in critical junctures and societal contradictions are beginning to create new crisis tendencies.